Understanding ITBS in Athletes: A Comprehensive Systematic Review - Alicja Grzelak (Quality in Sport)
Introduction: Iliotibial Band Syndrome (ITBS) is one of the most prevalent overuse injuries among athletes, particularly runners and cyclists. Characterized by lateral knee pain, ITBS often results from repetitive friction of the iliotibial band over the lateral femoral epicondyle, causing inflammation and discomfort. Despite its frequency, the mechanisms, risk factors, and effective interventions for ITBS remain topics of active investigation.